SPORTS PERFORMANCE. THE ANALYSIS OF THREE DISTURBING PSYCHOLOGICAL FACTORS (GYMNASIUM, 2009)
The performance is not born from an agglomeration of facts and happenings. It is a product of theeffects caused by concerted actions of objective and subjective factors.Performance serves to self-realization and self-assertion, representing a goal of man since ancienttimes until present.Harnessing the full potential of individual sportsman in order to obtain the best results is theaddiction to mental efficiency. Mental efficiency is based on self-knowledge and awareness of all the factorsthat can influence positively or not the process of preparation, on the way to achieve great performance.